Properties of ENR-50 based electrolyte system - Zainal, N.; Mohamed, N.S.; Idris, R. (Universiti Kebangsaan Malaysia, 2013)
In this work, epoxidized natural rubber 50 (ENR-50) has been used as a host polymer for the preparation of electrolyte system. Attenuated total reflection-fourier transform infrared spectroscopic analyses showed the presence of lithium salt-ENR interactions. The glass transition temperature displayed an increasing trend with the increase in salt concentration indicating that the ionic conductivity was not influenced by segmental motion of the ENR-50 chains. The increase in glass transition temperature with the addition of salt was due to the formation of transient cross-linking between ENR-50 chains via the coordinated interaction between ENR-50 chains and salt. The highest room temperature ionic conductivity obtained was in the order of 10-5 S cm-1 for the film containing 50 wt% of lithium salt. The ionic conductivity of this electrolyte system increased with increasing temperature and obeyed the Vogel-Tamman-Fulcher behavior. The increase in ionic conductivity of the electrolyte system with salt concentration could also be correlated to the charge carriers concentration and/or migration rate of charge carriers.